Palaeozoic ichnofossils in phyllites near Zelezny Brod, northern Bohemia - Chlupac,I. (Journal of the Czech Geological Society, 1997)
The epizonally metamorphosed roofing phyllites at Zelezny Brod, constituents of the Krkonose-Jizerske hory Metamorphic Complex (West Sudetes Unit of the Bohemian Massif), yielded Palaeozoic ichnofossils probably of Ordovician age. Typical are large stellate forms (”Teichichnus” stellatus) and branched traces Phycodes palmatus. Other traces belong to the ichnogenera Bifungites, Dictyodora, Lorenzinia, Megagrapton?, Planolites, Spirodesmos, Spirophycus, Taphrhelminthopsis and to some forms designated informally. The ichnoassemblage shows a deep-water character with relationships to the flysch facies.
Keywords: Ichnofossils; propably Ordovician; metamorphic rocks; phyllites; Bohemian Massif; West Sudetes Unit